1989
DOI: 10.1037/0022-0167.36.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizations of novice and experienced counselors.

Abstract: We examined the conceptualizations of 23 (II experienced and 12 novice) counselors, with respect to general counseling process and specific client concerns by means of a two-part conceptual mapping task (CMT). Analyses of the CMT data revealed an interaction effect of counselor experience and generality of conceptual task on the exlensiveness of counselor conceptualizations. Experienced counselors displayed slightly more extensive conceptualizations on the general CMT and less extensive conceptualizations on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 20 publications
2
74
0
1
Order By: Relevance
“…The differences are: (a) characteristics of a supervisee, such as anxiety level during counseling session (Hill, Charles, & Reed, 1981;Reising & Daniels, 1983); (b) expectations about supervision atmosphere and issues discussed, such as need for structure (Ellis, 1991;Heppner & Roehlke, 1984;Stoltenberg, Pierce, & McNeill, 1987); and (c) a supervisees' actual performance, for example, during a cognitive mapping task and in forming a working alliance (Mallinchrodt & Nelson, 1991;Martin, Slemon, Hiebert, Hallberg, & Cummings, 1989;Mayfield, Kardash, & Kivilighan, 1999). The differences are: (a) characteristics of a supervisee, such as anxiety level during counseling session (Hill, Charles, & Reed, 1981;Reising & Daniels, 1983); (b) expectations about supervision atmosphere and issues discussed, such as need for structure (Ellis, 1991;Heppner & Roehlke, 1984;Stoltenberg, Pierce, & McNeill, 1987); and (c) a supervisees' actual performance, for example, during a cognitive mapping task and in forming a working alliance (Mallinchrodt & Nelson, 1991;Martin, Slemon, Hiebert, Hallberg, & Cummings, 1989;Mayfield, Kardash, & Kivilighan, 1999).…”
mentioning
confidence: 99%
“…The differences are: (a) characteristics of a supervisee, such as anxiety level during counseling session (Hill, Charles, & Reed, 1981;Reising & Daniels, 1983); (b) expectations about supervision atmosphere and issues discussed, such as need for structure (Ellis, 1991;Heppner & Roehlke, 1984;Stoltenberg, Pierce, & McNeill, 1987); and (c) a supervisees' actual performance, for example, during a cognitive mapping task and in forming a working alliance (Mallinchrodt & Nelson, 1991;Martin, Slemon, Hiebert, Hallberg, & Cummings, 1989;Mayfield, Kardash, & Kivilighan, 1999). The differences are: (a) characteristics of a supervisee, such as anxiety level during counseling session (Hill, Charles, & Reed, 1981;Reising & Daniels, 1983); (b) expectations about supervision atmosphere and issues discussed, such as need for structure (Ellis, 1991;Heppner & Roehlke, 1984;Stoltenberg, Pierce, & McNeill, 1987); and (c) a supervisees' actual performance, for example, during a cognitive mapping task and in forming a working alliance (Mallinchrodt & Nelson, 1991;Martin, Slemon, Hiebert, Hallberg, & Cummings, 1989;Mayfield, Kardash, & Kivilighan, 1999).…”
mentioning
confidence: 99%
“…Early studies reported on the difficulties new counselors experience in this skill area. Martin, Slemon, Hiebert, Halberg, and Cummings (1989) found that gaining greater counseling experience gradually equips seasoned practitioners with the cognitive skills needed for efficient theory-driven client appraisal and case formulation. By comparison, newer clinicians tend to experience ambiguity and confusion as they begin the development of client appraisal (Loganbill, Hardy, & Delworth, 1982) and feel less confident about diagnosis, assessment, and client conceptualization (Glidewell & Livert, 1992;Ladany, Marotta, & Muse-Burke, 2001;Robbins & Zinni, 1988).…”
Section: Developing Case Management Skills: Clinical Assessment and Tmentioning
confidence: 99%
“…When working with real clients, clinicians may encounter several problems. For example, data can become available over a long time-period during the course of therapy; some clients may be less able or less willing to share all of the information that would be useful for practicing case conceptualization skills; supervisees and trainees may be limited by an agency's specific intake and recording procedures; the use of some skills may be inappropriate for some clients in certain settings; and the chance to work on case formulation skills is somewhat dependent on the clinician's existing skills at information gathering and conducting an intake (APA, 2000;Loganbill, Hardy, & Delworth, 1982;Martin et al, 1989). On the other hand, when using fictional or biographical characters as practice cases, all available information appears simultaneously for use in assessment, diagnosis, case formulation, and treatment planning.…”
Section: Using Popular Charactersmentioning
confidence: 99%
“…Uygulayıcı yetiştirmenin temel amaç olduğu psikolojik danışman eğitiminde psikolojik danışma uygulamaları oldukça önemli bir yer tutmaktadır (Martin, Slemon, Hiebert, Hallberg ve Cummings, 1989;McNeill, Stoltenberg ve Pierce, 1985). Bununla birlikte, ruh sağlığı uzmanlarının uygulama deneyimi kazanmaları büyük öneme sahip olsa da (Gustavson, Cundick ve Lambert, 1981); söz konusu uygulamalara yönelik süpervizyon süreci de psikolojik danışman eğitiminin ayrılmaz bir parçasıdır (Bernard ve Goodyear, 2004).…”
Section: Introductionunclassified